Effect of Ultrasonic Pretreatment on Flocculation Filtration of Low-Rank Coal Slurry - Aosheng Yang; Yinfei Liao; Maoyan An; Yijun Cao; Zhe Yang; Hourui Ren; Hailong Su; Qiqi Zou; Luojian Chen (Molecules, 2022)
The efficient filtration of low-rank coal (LRC) slurry was significantly beneficial to the production process of wet coal beneficiation. However, relatively few studies have been reported on novel pretreatment methods for the efficient filtration of LRC slurry. In this paper, the mechanism of ultrasonic pretreatment to promote flocculation and filtration of slurry was studied. The hydrophobic variation of the slurry surface was measured by contact angle and XPS. The flocculation properties of slurry were characterized using zeta potential and FBRM. The effects of filter cake porosity and ultrasonic pretreatment on slurry filtration resistance were calculated by L-F NMR and Darcy’s theory. The results showed that the ultrasonic pretreatment promoted the flocculation and filtration performance of LRC slurry, increased the filtration rate, and decreased the cake moisture content. Meanwhile, the contact angle of LRC increased significantly from 50.1° to 67.8° after ultrasonic pretreatment, and the surface tension of the filtrate decreased from 69.5 to 53.31 mN/m. Ultrasonic pretreatment reduced the absolute value of the zeta potential of coal slurry from 24.8 to 21.0 mV, and the average chord length of flocs increased from 5–10 μm to 25–30 μm, thus weakening the electrostatic repulsion between coals to promote floc formation. In addition, the pore tests and filtration theory calculations showed that the ultrasonic pretreatment significantly improved the permeability of the filter cake to water and reduced the resistance to slurry during filtration. In particular, the mesopore porosity increased by 9.18%, and the permeability increased by 2.937 × 108 m2. Therefore, this contributed to the reduction of slurry filtration resistance. This research provides an efficient method for promoting the efficient filtration of slurry.